Percutaneous endoscopic cervical discectomy: a technical review - Quillo-Olvera, Javier (Ann Transl Med, 2018)
The treatment of cervical disc herniations has evolved in the last 2 decades. While the anterior cervical discectomy and fusion continues being the gold standard for the treatment of radicular pain triggered by cervical disc herniation, other surgical approaches have been developed. Percutaneous endoscopic cervical discectomy has demonstrated the ability to decompress the exiting nerve root and dural sac correctly and encouraging clinical outcomes has been reported in the literature. One of the most important advantages offered by the endoscopic technique is the capability to resolve the patient’s symptoms without the need for interbody fusion. Also, a specific and selective decompression under continuous visualization with minimal surgery-related trauma can be achieved. There are two percutaneous endoscopic cervical discectomy approaches: anterior and posterior. The decision to perform each other depends on pathology site. However, the endoscopic technique requires previous surgical training, a steep learning curve, and proper patient selection. The development of new hardware such as endoscopes with better optics, lighting systems, and endoscopic surgical tools have allowed using endoscopic techniques in more complex cases. The objective of this review is the technical description of the anterior and posterior percutaneous endoscopic cervical discectomy.